Interpreting Brexit
V, 104 p. 2 illus.
Keywords: This volume examines the impact of Brexit on political traditions such as nationalism, liberalism and conservatism, cosmopolitanism and decentralization. Bringing together scholars of British Politics, the chapters focus on the following topics: Brexit and the myth of British National identity since World War II; the evolution of discourses surrounding Brexit and the broader shifts in the character of British liberal and conservative traditions; how the phenomenon of Brexit has decentered the Labour Party’s ideational tradition; the expression of beliefs about Brexit and British foreign policy; the ‘identity effects’ of Brexit on unionism and nationalism in Northern Ireland; whether the UK require a more decentred local government at a community level in order for people to feel both represented, and able to participate. Mark Bevir is Professor of Political Science in the Department of Political Science and Center for British Studies,University of California at Berkeley, USA. Matt Beech is Reader in Politics and Director of the Centre for British Politics, University of Hull, UK.